Análise dos casos da pandemia da COVID-19 no espaço paraense - COUTINHO, Jesus de Nazaré Melo (2023)
The present work deals with the impacts of the COVID-19 pandemic in the space of Pará, as well as the forms of prevention, combat, treatment of this disease which reached the world at the beginning of the third decade of the 21st century. Objective: to analyze the cases of infection by the SARSr-COV-2 virus with the help of cartography in the identification of the areas of incidence of covid-19 as well as the factors that contributed to the deaths that occurred during the pandemic in Pará. Methodology: this is a quantitative-descriptive epidemiological study of cases and deaths reported at the Pará State Health Department (SESPA). Results: COVID-19 has so far affected 842,533 confirmed cases and 18,876 deaths in Pará, 801,019 recovered cases, 55% of cases are female and 45% male, of the comorbidities that most contributed to the worsening of the disease were heart disease 2.82%, diabetes 2.17% and asthma 0.44%, young people and adults (20 to 49 years old) were the population most affected by the disease; the vaccination plan reached 16,315,281 doses applied out of a total of 18,160,924 doses sent by the Ministry of Health in an estimated population of 7,468,272 inhabitants in the State of Pará. Conclusion: the COVID-19 pandemic has brought numerous impacts to society and forced the government to draw up an action plan so that the public health system does not collapse to the point of not supporting the demand, forcing it to resignify itself each time. At a time when the situation became more tense than expected, government actions were essential for the population to have the essential access necessary to care for survival, the joint action of social actors (public authorities and society) is essential for effectiveness strategies for the control of pandemic diseases.